BUDAYA ORGANISASI SEKOLAH DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK PADA SMA NEGERI 1 KOTA LHOKSEUMAWE - Muhammad Iqbal; Niswanto .; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
ABSTRACTSchool organizational culture has an important role in realizing academic and non academic quality standards in schools. School organizational culture born of noble values embodied in a shared vision among all components of the school, an effective school organizational culture grows and develops continuously in the hope of providing characteristics for the development of the character of learners. in general, this study aims to describe the school organizational culture in the character formation of learners in SMA Negeri 1 Kota Lhokseumawe. Through the preparation of school culture formation programs, the implementation of school culture formation programs, as well as supporting and inhibiting factors in the establishment of school organizational culture. This research uses descriptive method with qualitative approach with data collection technique through observation, interview, and documentation study. Research subjects are element of school residents consisting of: principals, vice principals, vice principals, teachers, and learners. The results of the study showed that: (1) the program of establishing a school organizational culture containing religious programs (ROHIS), non-smoking and drug-free school programs, healthy and clean school culture, scouting programs, youth red cross, paskibraka program, PPPK) literacy program, extracurricular program for all subjects, and honesty canteen program; (2) the implementation of the school organizational culture formation program involves all stakeholders, the role and ability of all stakeholders, the results of the implementation of the school organizational culture program, the result (3) the inhibiting factors facing the school lack of faculty yag mastering scouting, male religion, lack of support from some teaching staff, there are parents of learners who are less supportive of school organizational culture values, and the influence of foreign culture and development of science and technology contributes negatively.Keywords: culture, school organization, and student character